Fear Appeal e Message Framing Strategie persuasive in interazione per la promozione della salute - Romani, Gianmarco (Premio Ricerca «Città di Firenze», 2013)
Our health is largely linked to our actions, habits and lifestyles. This implies greater personal and responsibility and, at an institutional level, the possibility and the obligation to act to prevent diseases and promote a healthy behaviour. Persuasive communication is one of the main tools for pursuing this goal. In fact, it has proven effective in promoting a change in attitudes, intentions and behaviours. Given these assumptions, the research investigates the possibility of simultaneously using two of the most effective communication strategies (fear appeal is message framing), evaluating which combination is more persuasive in promoting important preventive behaviour, such as the use of sunscreen.